2016
DOI: 10.1002/2016tc004252
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial patterns of sediment routing across the southeast margin of the Tibetan Plateau: Insights from detrital zircon

Abstract: The Cenozoic deposits of the Tibetan Plateau's southeastern margin are often cited as part of a continental‐scale river system connecting the Paleo‐Yangtze River with the Paleo‐Red River. Confirming the purported connection and any subsequent drainage reorganization has garnered significant attention and varied proposed ages for reorganization. This study presents detrital zircon U‐Pb ages and paleocurrents in Eocene to Pleistocene sedimentary basin deposits distributed over a broad area of the southeast Tibet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 139 publications
(205 reference statements)
10
83
2
Order By: Relevance
“…Samples from the modern Yangtze River show that detrital K-feldspars characteristic of the lower Jinsha River are present at least as far as Yichang (Figure 3f), implying a similar potential transport distance if the lower Jinsha used to join the paleo-Red River. Our conclusion is supported by recent detrital zircon geochronology from Cenozoic sediments, which indicates that the provenance for both onshore and offshore deposits can be explained by local bedrock sources, and thus, any connection between the Yangtze and Red Rivers must have occurred before the Eocene [Wissink et al, 2016].…”
Section: Provenance Of the Paleo-red Riversupporting
confidence: 73%
See 1 more Smart Citation
“…Samples from the modern Yangtze River show that detrital K-feldspars characteristic of the lower Jinsha River are present at least as far as Yichang (Figure 3f), implying a similar potential transport distance if the lower Jinsha used to join the paleo-Red River. Our conclusion is supported by recent detrital zircon geochronology from Cenozoic sediments, which indicates that the provenance for both onshore and offshore deposits can be explained by local bedrock sources, and thus, any connection between the Yangtze and Red Rivers must have occurred before the Eocene [Wissink et al, 2016].…”
Section: Provenance Of the Paleo-red Riversupporting
confidence: 73%
“…Though thermochronological data from SE Tibet indicated that major topographic uplift occurred after the Oligocene to early Miocene [Clark et al, 2005;Kirby et al, 2002;Wang et al, 2012], provenance work in the Jianchuan Basin (Figure 1b) suggested that a large river originating from the Songpan-Ganzi used to drain southwestward during the late Eocene [Yan et al, 2012]. Our conclusion is supported by recent detrital zircon geochronology from Cenozoic sediments, which indicates that the provenance for both onshore and offshore deposits can be explained by local bedrock sources, and thus, any connection between the Yangtze and Red Rivers must have occurred before the Eocene [Wissink et al, 2016]. Samples from the modern Yangtze River show that detrital K-feldspars characteristic of the lower Jinsha River are present at least as far as Yichang (Figure 3f), implying a similar potential transport distance if the lower Jinsha used to join the paleo-Red River.…”
Section: Geophysical Research Letterssupporting
confidence: 62%
“…However, these authors did not elucidate how the river incision was genetically linked with evolution of local rivers (e.g., Jinsha River) and which transpressional structure(s) could account for the exhumation. Whether the ancient Jinsha River flowed through the Jianchuan basin is largely disputed (e.g., Clark et al, ; Wei et al, ; Wissink et al, ). Eocene fluvial sediments of the Baoxiangsi Fm.…”
Section: Discussionmentioning
confidence: 99%
“…Despite disagreements on the patterns and timing of its reorganization, drainage capture of the paleo-Red River is proposed to have occurred from the Paleocene to the middle Miocene (Chen et al, 2017;Clift, Blusztajn, & Nguyen, 2006;Clift et al, 2008;Hoang et al, 2009;Zheng et al, 2013). Recent observations, however, argue against large-scale river capture (Wei et al, 2016;Wissink et al, 2016;Yan et al, 2011;Zhang et al, 2019;Zhao et al, 2015). The paleo-drainage patterns and timing of major drainage reorganization of the Red River represent a major question that has implications for the timing of orogenic uplift and sediment provenance.…”
Section: Introductionmentioning
confidence: 99%